Inflammatory and neuropathological responses to Vesiculovirus carajas encephalitis in adult mice: variability, tolerance and resistance - Cavalcante, Maria Sueli Barbosa; Santos, Diego Siqueira; Araújo, Lidineuza Machado; Freitas, Priscilla Lieuthier; Silva, Carlos Augusto Moreira; Carvalho, Karina Glazianne Barbosa; Araújo, Marialva Tereza Ferreira; Silva, Eliana Viera Pinto da; Rodrigues de Farias, Ana Paula Drummond; Guerreiro Diniz, Daniel; Picanço Diniz, Cristovam Wanderley; Diniz, José Antonio Picanço (Frontiers in Cellular and Infection Microbiology, 2025)
Vesiculovirus carajas (CARV) is a pathogen with neuroinvasive potential, yet its impact on neuroinflammation and sickness behavior remains poorly understood. In this study, we investigated the neuropathological and immunological responses to CARV encephalitis in adult BALB/c mice. Mice were intranasally inoculated with either infected or uninfected brain homogenates, and clinical, histopathological, and cytokine profiles were analyzed. CARV antigens were primarily detected in necrotic neurons, with prominent microglial activation near the ventricles and blood vessels. By day 10 post-infection, infected mice exhibited significantly elevated levels of MCP-1, IFN-γ, IL-12 p70, TNF-α, IL-6, and IL-10 in the brain, indicating a strong inflammatory response. These findings highlight the inflammatory modulation associated with CARV infection and suggest a hematogenous route of neuroinvasion, distinguishing CARV from other vesiculovirus species. This study provides new insights into the pathogenesis of CARV encephalitis and its potential impact on neuroimmune dynamics.